Sikap Dan Motivasi Pelajar Ipt Terhadap Modul Pengajaran Bahasa Arab Pelancongan - M. Najib, J.; Kirembwe, Rashid A. H.; Lubna, A. R.; Zainur Rijal Abdul Razak (Kolej Universiti Islam Sultan Azlan Shah, 2024)
The purpose of this study was to know the effectiveness of teaching module of Arabic For Tourism Purposes at several public and private Institutes of Higher Education in Malaysia. This study was carried out involving 126 students from USIM, UiTM and KUIS which offer the Arabic For Tourism subject including 30 male students and 96 female students. The results has shown the percentage of attitude and motivation levels towards Teaching Module of Arabic For Tourism was high about 90%. The result has also shown the effectiveness of this module with mean score = 3.63 dan sd. = 0.65. More than 85% of the respondents agreed that this module can be applied into career planning in the tourism sector. The reliability of the instrument was high with Cronbach Alfa= 0.96.